O estágio supervisionado como contexto de formação docente específica para educação infantil: o que dizem os formandos sobre suas aprendizagens? - Melo, Jacicleide Ferreira Targino da Cruz (2014)
Kindergarten teachers training gains the spotlight with the passing of Law number 9.394/96 (Guidelines and Basis Law) that defines this segment as the initial step of basic education, with pedagogical function. In this spectrum, the discussion about teacher training unravels to ensure social quality to education as well as the teacher s specificities towards child singularities. Adding to that, the growing propagation of Pedagogy in an undergraduate level, given that such course has been continually transformed by the National Curriculum Guidelines for Pedagogy (2006), highlighting the addition of curriculum components that are specific to upbringing. The complex debate circa kindergarten teachers training has advancements and hardships that need to be unveiled in order to improve both formation and social quality of education in the 0- 5 years old range. This investigation inserts itself in said context and aims to analyze which knowledge, specific to kindergarten teaching are constructed, according to undergraduate trainees, in Pedagogy s supervised internship. The study was conducted alongside the discipline: Supervised Internship in Child Education ministered by the Advanced Campus of Rio Grande do Norte s State University s in the municipality of Patu-RN (CAP-UERN-Patu) and was conducted through 2012 by accompanying four undergraduate interns. We first assumed that the development of teaching knowledge is a complex process of appropriation of cultural-social practices and is symbolically mediated by interactions that occur in the formation context, and the supervised internship can be understood as a space for the articulation and enlargement of theoretical and practical knowledge, directly related to the specificities of child education. The theoretical-methodological foundation was based upon the historiccultural approach of L. S. Vygotsky and M. Bakhtin s dialogism on human sciences research, as well as his postulates on learning and developmental processes, conceived as both essentially social and discursive. The investigation approached the principles of the qualitative perspective and to the construction and analysis of data, involved documental analysis and, specially, semi-structured interviews, both individual and collective, whose fundamental premise was the production-comprehension of meanings in a dialogical perspective. The participants texts/speeches produced a synthesis that points to the occurrence, within the supervised internship at CAP/UERN, of internalization/appropriation processes and, as such, of formulation of meanings that are pertinent to child education: child, childhood, kindergarten and teacher signification and this stage s specific teaching knowledge. It stood out that the internship, alongside other curriculum components, is, in fact, one of the primeval formation environment for the teachers, in which the interns interact with their colleagues, supervisor professor, collaborator professor, and of course, the children to construct their erudition. Such interactions allow the undergraduate interns to develop attitudes and procedures to reflect on what they know, what they ve done and what they can achieve. We have concluded that the undergraduate internship can constitute itself as an articulatorconsolidator environment in the future teacher s formation process and, since well oriented, can provide the effective initiation, not only to the practice, but to the praxis as a movement of non dissociability between theory and practice